Contralateral motor deficit in extradural hematoma: Analysis of 35 patients - Husain, Mazhar; Ojha, BK; Chandra, Anil; Singh, Anoop; Singh, Gurpreet; Chugh, Ashish; Rastogi, Manu; Singh, Kamlesh (Indian Journal of Neurotrauma, 2007)
We work at one of the busiest trauma centers of the country and deal with more than 200 cases of extradural hematomas per year. The striking frequency of the association of motor deficits with extradural hematomas prompted us to take up this study and delineate the factors that could lessen the morbidity by decreasing the convalescence of the affected patients. We primarily found that the association between EDH and motor deficits was common, and early intervention resulted in faster recovery of motor power, (70% in patients operated within 24 hours of trauma, and 53.3% in patients operated after 24 hours of trauma. recovered complete power within 4 weeks.) We concluded a clinically significant association of extradural hematomas and concurrent motor deficits, and found that timely intervention in patients presenting with mild head injury enabled us to achieve complete recovery of motor power. Contributing factors included the concurrence of signs of herniation and associated parenchymal injuries.
Keywords: extradural hematoma; head injury